2014
DOI: 10.1128/jvi.00761-14
|View full text |Cite
|
Sign up to set email alerts
|

SnRK1 Phosphorylation of AL2 Delays Cabbage Leaf Curl Virus Infection in Arabidopsis

Abstract: Geminivirus AL2/C2 proteins play key roles in establishing infection and causing disease in their plant hosts. They are involved in viral gene expression, counter host defenses by suppressing transcriptional gene silencing, and interfere with the host signaling involved in pathogen resistance. We report here that begomovirus and curtovirus AL2/C2 proteins interact strongly with host geminivirus Rep-interacting kinases (GRIKs), which are upstream activating kinases of the protein kinase SnRK1, a global regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 60 publications
4
52
0
Order By: Relevance
“…For example, the begomovirus nuclear shuttle protein (NSP)-interacting kinase 1 (NIK1) is able to activate antiviral immunity against cabbage leaf curl virus (CaLCuV) (25,26). Besides the above-mentioned defense mechanisms, host factors such as SNF1-related protein kinase 1 (SnRK1) have also been involved in defense against geminiviruses (27)(28)(29).…”
mentioning
confidence: 99%
“…For example, the begomovirus nuclear shuttle protein (NSP)-interacting kinase 1 (NIK1) is able to activate antiviral immunity against cabbage leaf curl virus (CaLCuV) (25,26). Besides the above-mentioned defense mechanisms, host factors such as SNF1-related protein kinase 1 (SnRK1) have also been involved in defense against geminiviruses (27)(28)(29).…”
mentioning
confidence: 99%
“…A further control experiment with a frameshift mutant of HA:AC2 completely excluded promoter and RNA effects as the relevant causes. Although AC2 expression was improved by the avoidance of PTGS, the level of protein was still very low, an experience which was also mentioned recently by other authors (18). Therefore, we believe that this is a more general problem, which is solved for the first time in this study.…”
Section: Discussionmentioning
confidence: 47%
“…The charge parameter can be further modulated by posttranscriptional modifications such as phosphorylation. Interestingly, Shen et al (18) found a differential phosphorylation of AC2 by SnRK, a signaling kinase involved in regulating sugar metabolism (76,77), dependent on the geminivirus species. This implies a change of the AC2 charge in the dependence of the carbohydrate level and a fine-tuning of its effect on replication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations